Relation of leg phase angle from bioelectrical impedance analysis with voluntary and evoked contractile properties of the plantar flexors - Hirata, Kosuke; Yamada, Yosuke; Iida, Natsuki; Kanda, Akihiro; Shoji, Mikio; Yoshida, Tsukasa; Akagi, Ryota (Frontiers in Physiology, 2023)
Bioelectrical impedance analysis (BIA) can noninvasively and quickly assess electrical properties of the body, such as the phase angle. Phase angle is regarded as the quantity and/or quality of skeletal muscle and is associated with exercise performance, such as jump height and walking speed. Although the phase angle derived from BIA is assumed to be a useful way to assess muscle function, the relationship between the phase angle and neuromuscular properties has not been fully investigated. The purpose of this study was to investigate the association of phase angle with voluntary and evoked contractile properties in 60 adults (age, 21-83 years; 30 females and 30 males). The phase angle of the right leg at 50 kHz was evaluated using BIA. The twitch contractile properties (peak twitch torque [PTtwitch], rate of twitch torque development [RTDtwitch], and time-to-PTtwitch [TPTtwitch]) of the plantar flexors were measured using tibial nerve electrical stimulation. Maximal voluntary isometric contractions (MVICs) were performed to measure the maximal muscle strength and explosive muscle strength, from which the peak MVIC torque (PTMVIC) and rate of torque development (RTD) over a time interval of 0-200 ms were assessed, respectively. The root mean square (RMS) values of electromyographic (EMG) activity during the PTMVIC and RTD measurements (EMG-RMSMVIC and EMG-RMSRTD, respectively) were calculated. The RTD and Phase angle and neuromuscular properties 2 EMG-RMSRTD were normalized using PTMVIC and EMG-RMSMVIC, respectively. Phase angle significantly correlated with twitch contractile properties (|r|≥0.444, P<0.001), PTMVIC (r=0.532, P<0.001), and RTD (r=0.514, P<0.001), but not with normalized RTD (r=0.242, P=0.065) or normalized EMG-RMSRTD (r=−0.055, P=0.676). When comparing measurement variables between the low-and high-phase angle groups while controlling for sex and age effects, the high-phase angle group showed greater PTtwitch, RTDtwitch, PTMVIC, and RTD (P<0.001) and shorter TPTtwitch (P<0.001) but not normalized RTD (P=0.184) or normalized EMG-RMSRTD (P=0.317). These results suggest that the leg phase angle can be an indicator of voluntary and evoked muscle contractile properties but not the neuromuscular activity of the plantar flexors, irrespective of sex and age.